Gender Representation and Equality in Children’s Digital Storybooks: A Qualitative Content Analysis of Let’s Read Asia - Eka Amori Haydi Dhisa Tambong; Alief Noor Farida (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study applies a feminist-informed qualitative content analysis framework combined with a rubric-based gender equality evaluation aligned with Sustainable Development Goal 5 (Gender Equality) to examine gender representation in children’s stories published on the Let’s Read Asia platform. Thirty English-language narratives intended for learners in Grades 2–4 were systematically analyzed with respect to character prominence, gendered roles and occupations, narrative agency, and stereotypical or counter-stereotypical traits. The analytical rubric operationalized gender equality through five indicators: balance of character representation, diversity of social roles, degree of agency, portrayal of character traits, and narrative outcomes, enabling a structured comparison across texts. The findings indicate a measurable shift toward more equitable gender representation, with female characters occupying a slightly higher proportion of protagonist roles (52%) than male characters (45%). Beyond character frequency, the analysis reveals substantive changes in narrative function: contemporary stories increasingly depict female characters as professionals, problem-solvers, and leaders, challenging traditional gender-role associations. However, this pattern is not uniform. Traditional folktales continue to privilege male authority and heroic agency while positioning female characters in passive or domestic roles, indicating the persistence of patriarchal narrative structures. Using the gender equality rubric, 57% of the analyzed stories were classified as actively promoting gender equality, while the remainder were categorized as neutral or inequality-reinforcing. The study’s contribution extends beyond descriptive statistics by demonstrating how rubric-based analysis can systematically identify ideological shifts and continuities within digital children’s literature. By linking textual patterns to pedagogical implications, this research provides an evaluative framework for selecting and critically using digital storybooks in English language teaching contexts, particularly those seeking to align literacy instruction with inclusive education and gender equity principles.